Do You Speak Global?: The Spread of English and the Implications for English Language Teaching - Tonje M. Caine (Canadian Society for Studies in Education, 2008)
The spread of English as an international language has changed our conception of both the language and how it should be taught. With more nonnative than native speakers of English, the ownership of English has shifted and new world Englishes (WE) have emerged. Researchers studying this phenomenon have recommended changes to English language teaching (ELT) that require re-examining firmly entrenched assumptions still evidenced in teaching practice. Despite compelling evidence, English language teaching professionals have yet to embrace and enact researchers' recommendations. This article first examines the spread of English, then discusses its implications for ELT. The example of recommended changes for ELT enacted at Chukyo University in the Expanding Circle country of Japan illustrates changes that should be espoused by professionals worldwide.